2012
DOI: 10.1088/1742-5468/2012/04/p04008
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the packing fraction on the jamming of granular flow through small apertures

Abstract: Abstract. We investigate the flow and jamming through small apertures of a column of granular disks via a pseudo-dynamic model. We focus on the effect that the preparation of the granular assembly has on the size of the avalanches obtained. Ensembles of packings with different mean packing fractions are created by tapping the system at different intensities. Surprisingly, packing fraction is not a good indicator of the ability of the deposit to jam a given orifice. Different mean avalanche sizes are obtained f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…Only a careful preparation of the initial φ before the very first burst might be controlled (see Ref. 41 ). Of course, it is expected that a system with extremely low packing fraction will never develop clogging, but in this case the value of C L at the bottleneck will also approach zero.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Only a careful preparation of the initial φ before the very first burst might be controlled (see Ref. 41 ). Of course, it is expected that a system with extremely low packing fraction will never develop clogging, but in this case the value of C L at the bottleneck will also approach zero.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Of more direct relevance for our work is the study of intermittency in the mass discharge rate. For example, Uñac and co-workers found both fluctuations and characteristic time scales growing with decreasing hole size [34]. However, Janda and co-authors found no such behavior [35].…”
Section: Prior Experimentsmentioning
confidence: 99%
“…In our case the silo is emptied and refilled with the aperture closed, which is opened only after the grains are static. Uñac et al [12] have conducted a similar type of protocol as the one used here, but the system is tapped before opening the aperture to achieve a desired initial packing fraction. They found that clogging maw vary dramatically depending on the initial packing fraction before starting the avalanche.…”
Section: Resultsmentioning
confidence: 99%